2021
DOI: 10.3390/ijms22052738
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Overexpressed Genes in Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a fatal tumor lacking effective therapies. The characterization of overexpressed genes could constitute a strategy for identifying drivers of tumor progression as targets for novel therapies. Thus, we performed an integrated gene-expression analysis on RNAseq data of 85 MPM patients from TCGA dataset and reference samples from the GEO. The gene list was further refined by using published studies, a functional enrichment analysis, and the correlation between expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Therefore, regulation of each individual gene expression and its signalling pathways might potentially control EMT process thus leading to development of novel strategies for MESO therapeutics. SPARC protein has been observed upregulated in MESO cell lines 46 . Transcriptomic studies have identified that EMT-linked genes may contribute towards the resistance of chemotherapy and immunotherapy, suggesting that targeting EMT genes may be potentially applied to treat MESO patients 47 .…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, regulation of each individual gene expression and its signalling pathways might potentially control EMT process thus leading to development of novel strategies for MESO therapeutics. SPARC protein has been observed upregulated in MESO cell lines 46 . Transcriptomic studies have identified that EMT-linked genes may contribute towards the resistance of chemotherapy and immunotherapy, suggesting that targeting EMT genes may be potentially applied to treat MESO patients 47 .…”
Section: Discussionmentioning
confidence: 95%
“…BAP1 may also be a possible therapeutic target for precision medicine and prognostic biomarkers, being frequently altered in MM ( 29 ) together with other targets reported thus far ( 30 , 31 ). The 15th conference of the International Mesothelioma Interest Group (iMig), held in May 2021, demonstrated the usefulness of pleural effusions for the early diagnosis of MM.…”
Section: Discussionmentioning
confidence: 98%
“…No previous report has indicated that MPM expresses PHGDH or TRIM29 [ 12 , 13 , 18 ]. Nevertheless, both PHGDH and TRIM29 showed better immunohistochemical specificity and sensitivity than expected, despite the use of antibodies that are not really suited for routine FFPE immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, gene expression profiling (GEP) technology has become a key tool for the discovery of novel biomarkers [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], and it is readily applicable for analysis based on formalin-fixed paraffin-embedded (FFPE) tissues [ 14 , 15 ]. We have encountered a very rare example of a synchronous collision tumor consisting of both malignant pleural mesothelioma (MPM) and pulmonary adenocarcinoma (PAC) lesions, each of which showed the typical morphology and immunophenotype.…”
Section: Introductionmentioning
confidence: 99%